IDENTIFIKASI HORISON ARGILIK DENGAN METODE IRISAN TIPIS PADA ULTISOL DI ARBORETUM USU KWALA BEKALA - Christian Natanael Tarigan; Purba Marpaung; Kemala Sari Lubis (Jurnal Agroekoteknologi, 2014)
Identification argillic for reddish brown of podzolic soil (Ultisol) was conducted at Arboretum USUKwala Bekala, Deli Serdang Regency (50 meters above sea level). The research was conducted InJanuary - April 2013 by using thin section method to identification clay skin at each horizons layerby using a microscope petrothin. The results showed that no clay skin at horizons of ultisol fromArboretum USU Kwala Bekala Pancur Batu District , Deli Serdang Regency . it’s not true that bthorizon of ultisols is argillic. Land of arboretum USU Kwala Bekala more suitable as inceptisolsorder with cambic horizonKeywords: thin section, ultisol, argillic